Relationship between Family Support and Elderly Visits at the Elderly Posyandu in Liu Mulang Village, Long Pahangai District - Natalia Huring; Ismansyah; Rivan Firdaus (PT FORMOSA CENDEKIA GLOBAL, 2023)
Efforts to optimize the health status of the elderly in the community through the elderly posyandu program have been designed and applied but still found lack of utilization of these services. This type of research is quantitative and The population is the elderly in Liu Mulang Village, Long Pahangai District, totaling 52 people. The research was conducted at the elderly Posyandu in Liu Mulang Village, Long Pahangai District in March 2023. Characteristics of respondents mostly from respondents aged between 60-65 years (73.1%), male sex (55.8%), high school graduation education (61.5%), and not working/retirement (34, 6%).Family support to visit the elderly posyandu in the elderly lacks (53.8%) and the elderly visit to the elderly posyandu is not routine (55.8%).There is a relationship between family support and elderly visit (p value 0.030). it means there is a relationship between family support and elderly visits to the elderly Posyandu.